Exploring the Feasibility of a Comprehensive Screening for Voice and Swallowing Function in Post-Extubation Patients: A Pilot Study - Fernanda Figueroa-Martínez; Adrián Castillo-Allendes; Karla Grunewaldt; Tamara Solís-Meza; Eric J Hunter; Jeff Searl (Revista de Investigación e Innovación en Ciencias de la Salud, 2023)
Objectives. This pilot study aimed to identify and test a battery of time-efficient and cost-effective voice and swallowing screening tools for post-extubated patients in Chile.